ANTESEN CUSTOMER LOYALTY PADA BUDGET HOTEL - Latifa Rahma (Jurnal Manajemen dan Pemasaran Jasa, 2015)
This research discusses the effects of Service Quality on Customer Satisfaction, Customer Loyalty, and Brand Image Budget hotel (Five Budget Hotel Managed by local chain hotel). The purpose of this study were 1) to analyze the effects of Service Quality on Customer Satisfaction, 2) to analyze the effects of Service Quality on Customer Loyalty, 3) to analyze the effect of Customer Satisfaction to Customer Loyalty, 4) to analyze the effects of Service Quality on the Brand Image, 5 ) to analyze the influence of the Customer Satisfaction Brand Image, 6) to analyze the effect of Customer Loyalty to Brand Image. The design of this research using primary data obtained by distributing questionnaires to 250 respondents eligible stayed at the Budget Hotel at least 1 time in last 12 months. Respondents were selected using purposive sampling method and the data were analyzed using AMOS version 22.0 and SPSS version 22.0. The proposed model was tested using Structural Equation Modeling (SEM) and analyzed using AMOS. This study shows that 1) Service Quality found to have an influence on Customer Satisfaction, 2) Service Quality found to have an influence on Customer Loyalty, 3) Customer Satisfaction is found to have an influence on Customer Loyalty, 4) Service Quality found to have an influence on brand image, 5) Customer Satisfaction is found to have an influence on Brand Image, 6) Customer Loyalty found to have an influence on the Brand Image. The results of this study concluded that there is a positive influence of the Service Quality on Brand Image through the Customer Satisfaction and Customer Loyalty. Future researches are recommended to increase the factor of First Impression, Favorable Location, Hotel Core Product and Hotel Deals. Not only on the Budget Hotel research, but also be able to develop this research in the other service company such as travel, restaurant and hospital.